2019
DOI: 10.7554/elife.42068
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genomic architecture of a complex trait locus in hypertensive rat models links Tmem63c to kidney damage

Abstract: Unraveling the genetic susceptibility of complex diseases such as chronic kidney disease remains challenging. Here, we used inbred rat models of kidney damage associated with elevated blood pressure for the comprehensive analysis of a major albuminuria susceptibility locus detected in these models. We characterized its genomic architecture by congenic substitution mapping, targeted next-generation sequencing, and compartment-specific RNA sequencing analysis in isolated glomeruli. This led to prioritization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 80 publications
5
35
0
Order By: Relevance
“…Moreover, TMEM63C expression was found to be modulated by TGF-β stimulation in kidney cells. In addition to previous data [7], our data indicate that TMEM63C could be involved not only in GFB function but also in EMT.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Moreover, TMEM63C expression was found to be modulated by TGF-β stimulation in kidney cells. In addition to previous data [7], our data indicate that TMEM63C could be involved not only in GFB function but also in EMT.…”
Section: Discussionsupporting
confidence: 81%
“…Schulz et al [7] showed the importance of TMEM63C expression for the maintenance of GFB in zebra fish models and demonstrated its potential relevance in patients with focal segmental glomerulosclerosis in translational studies. However, until now, the expression regulation of TMEM63C is widely unexplored.…”
Section: Expression Regulation and Functional Effects Of Tmem63c In Hmentioning
confidence: 99%
See 3 more Smart Citations